Visibility, wind speed, and dew point temperature are important factors in SARS‐CoV‐2 transmissibility. (20th April 2022) - Zhou, Dansha; Wang, Elizabeth W.; Hou, Chi; Liao, Jing; Zhang, Jiarui; Fu, Xin; Chen, Jiyuan; Xing, Yue; Hong, Wei; Zhang, Zhe; Chen, Yuanwei; Feng, Huazhuo; et al.
Abstract: The aim of this study is to provide evidence for the influencing factors of severe acute respiratory syndrome coronavirus 2 (SARS‐COV‐2) virus mutation by determining the impact of geographical and meteorological factors on SARS‐CoV‐2 transmission, and the different impacts of SARS‐CoV‐2 variant strains. From January 20 to March 10, 2020, we collected a number of daily confirmed new cases and meteorological factors in all cities and regions in China and Italy affected by the Alpha "variants of concern" (VOC). We also collected the daily confirmed cases of the Delta VOC infection in China and Italy from May 21 to November 30, 2021. The relationships between daily meteorological data and daily verified new cases of SARS‐CoV‐2 transmission were then investigated using a general additive model (GAM) with a log link function and Poisson family. The results revealed that latitude was substantially connected with daily confirmed new instances of the Alpha VOC, while there was no such correlation with Delta VOC transmission. When visibility is greater than 7 m, the propagation of the Alpha and Delta VOCs in Italy and China can be controlled. Furthermore, greater temperatures and increased wind speed reduce the transmission of the Alpha and Delta VOCs. In conclusion, geographical and meteorological factors play an important role in SARS‐CoV‐2 transmissibility and should be considered in virus mitigation strategies.